Healthy lifestyle and recommendations in health care among hypertensive and diabetic patients in Brazil, 2019 - Célia Landmann Szwarcwald; Paulo Roberto Borges de Souza Júnior; Giseli Nogueira Damacena; Sheila Rizzato Stopa; Marilisa Berti de Azevedo Barros; Deborah Carvalho Malta
ABSTRACT Objective: To estimate prevalence of healthy behaviors among individuals aged 30 years or more, diagnosed with arterial hypertension and diabetes mellitus, using information from the National Health Survey, 2019. Methods: Cross-sectional study with cluster sampling and simple random sampling in three stages. Individuals were aggregated according the following conditions: having arterial hypertension; arterial hypertension only; diabetes mellitus; diabetes mellitus only; arterial hypertension and diabetes mellitus only; without chronic non-communicable diseases. Poisson regression models and crude and adjusted prevalence ratios for sex, age group, and schooling were used. The proportion of recommendations received by patients with arterial hypertension and diabetes mellitus was estimated by type of care (public/private). Results: A total of 69,285 individuals aged 30 years or more was analyzed. Compared to individuals without non-communicable diseases, prevalence of consumption of fruits and vegetables ≥5 days a week was significantly higher among individuals with arterial hypertension (39.9% - 95%CI 38.8-41.0) and those with diabetes mellitus (42.8% - 95%CI 40.7-44.9). However, estimates of not having consumed ultra-processed food were low, 19.7% (95%CI 18.9-20.6) and 21.9% (95%CI 20,3-23.5), respectively. Prevalence of not smoking reached values close to 90% and significant prevalence ratios, whereas the practice of physical activity had levels below 30% and non-significant prevalence ratios. The proportion of healthy eating recommendations reached 90%, but it was close to 70% for not smoking. Conclusions: It is necessary to encourage the practice of healthy lifestyles and provide information about the benefits of physical activity and the harmful effects of unhealthy eating for well-being and aging with quality.